Product management and product elimination - Harness, David (Henry Stewart Talks, 2008)
The financial services product, Service product attributes, Challenges caused by service product characteristics, Product management, Product lifecycle, End stage product management, Causes of product elimination, Identification of an elimination candidate, Removal process, Product elimination stage model